PEMBERDAYAAN EKONOMI MASYARAKAT MELALUI PENGEMBANGAN EKONOMI REMAJA MASJID - Waluyo Waluyo; Yulfan Arif Nurohman; Rina Sari Qurniawati (Sekolah Tinggi Ilmu Ekonomi AMA, 2023)
People's hopes of getting a better life can be done by developing the economy. One way to develop the economy is by developing livestock businesses. Village communities who work as farmers often experience economic difficulties so solutions need to be provided to help the family economy. Mosque youth have the potential to be provided with economic development programs through goat seed waqf. Mosque youth as the next generation have greater opportunities for economic development in the future. The aim of the community service program implemented in Tempuran Village is to improve the economy through goat seed waqf. The community service program is divided into four stages. Starting from deepening the problem, focus group discussions determining material, training; and mentoring. The results of this program provide the benefit of increasing income for the community in Tempuran Village by optimizing the goat seed waqf.